PERENCANAAN DAN PENGENDALIAN KAPASITAS WAKTU PRODUKSI DENGAN METODE ROUGH CUT CAPACITY PLANNING PADA SISTEM INFORMASI DI PERCETAKAN MAXIMEM - Rifdan Muntaqi; Anton Setiawan Honggowibowo; Dwi Nugraheny (Compiler, 2013)
The increasing consumer demand for printing services that utilize existing capacity resulting in an imbalance in the production floor. When orders come in, the company has always approved the transaction without first reviewing the available resources. Time capacity planning and control is one very important element in decision-making. On research planning and control of production capacity using the data available capacity in each period and the capacity required to fulfill orders in the period.Capacity Planning and Control Production Time Rough Cut Capacity Planning Methods to determine the estimated processing time, capacity reports, and decisions o f the order. The test results o f the 30 respondents apilkasi display application users are 67%, 70% users ease, clarity of information and data is 80%, 57% apilkasi usefulness, 80% rated the overall application. Thus, the Capacity Planning and Control Of Time With Rough Cut Capacity Planning Method Information System At Maximem Printing use this app either.